Aspects of political ideas & institutions in ancient India - "Sharma, Ram Sharan" (Delhi, 1959)
In 1951, when Political Thought and Administration in Ancient India was introduced as a special paper at the M.A. stage in History at the Patna University, I began a more careful study of the subject for lecturing to my students. In course of my pursuit I discovered that in spite of two dozen monographs on the subject there was scope for new lines of enquiry. The following pages, therefore, embody the results of that investi gation and are intended to focus light only on those problems which are considered rather obscure or need to be studied de novo. About one half of this book has already been pub lished in the form of articles. But for the purpose of the present work those essays have been re-touched, edited and brought into some sort of relation with the additional material, both in form and substance. The chapters dealing exclusively with political ideas have been put at the beginning, and the others have been arranged in chronological order. In the case of the discussion of the origins of feudalism, its economic aspects, though not quite relevant to the theme of the book, have also been taken into account. Although the book, as it has emerged, can hardly be regarded a coherent study of the subject, it is not without some connecting threads and assump tions.
Keywords: Political Science